Analisis Filosofi Ungkapan Bere Secupak, Ikan Sejerek Madar pada Masyarakat Pesisir Kota Bengkulu - Atdi Maseta Prones (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2023)
Coastal Society. In this paper, the author invites the reader to find out how the philosophy of bere secupak, fish sejerek, madar applies to the coastal communities of Bengkulu city. The problem in this research is what is the philosophical meaning of the expression bere secupak, fish sejerek madar? This research is included in the type of field research (field research) based on the data that appears in the form of words and not a series of numbers. The method used is descriptive qualitative method and the approach used in this research is the phenomenological approach. The application of this research method began with the preparation of research, the implementation of data collection and data analysis. Data collection was carried out by observative participatory, interview, and documentation. Data analysis in qualitative research generally starts from data collection, data reduction, concentration, abstracting and transformation of rough data that emerge from records in the field. Data display was performed using narrative text form, drawing conclusions, and verification. The results showed the essence of the philosophical meaning of the expression bere secupak, fish sejerek, madar symbolizing the character of Bengkulu people who have a high work ethic, are not lazy, have principles and are responsible. This philosophy also contains the meaning of simplicity, symbolizing the concept of gratitude, the concept of tawakal, and the concept of balance in order to reach the life of the world and the hereafter. As for the application of this philosophy there is still a dualism of meaning that develops in the community, people who think positively about this meaning, see more of the context implied in the philosophy. While those who think negatively about the philosophy tend to interpret the philosophy textually, so that people are fooled to the text of the expression rather than the meaning implied in the expression.